2019
DOI: 10.2174/1574887114666190620112829
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Tranexamic Acid for Subdural and Epidural Intracranial Hemorrhage: Randomized, Double‐Blind, Placebo-Controlled Trial

Abstract: Background: Recovery of patients with traumatic brain injury largely depends on the reduction in secondary brain damage. The present study aims at investigating the effect of Tranexamic Acid (TXA) administration within the first hours of brain trauma in the emergency department (ED). Methods: This randomized, double-blind, placebo-controlled clinical trial was carried out in patients with subdural and epidural hemorrhage. Patients with any type of bleeding were assigned into two groups of TXA and 0.9% normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Aside from the included studies, there was an observational study reported that TXA administration in patients with cerebral contusions or traumatic subarachnoid hemorrhage was independently associated with a reduced mortality rate [22]. An RCT showed that TXA was associated with reduced intraoperative bleeding but not hemoglobin change in patients with epidural, subdural, and intraparenchymal hemorrhage [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the included studies, there was an observational study reported that TXA administration in patients with cerebral contusions or traumatic subarachnoid hemorrhage was independently associated with a reduced mortality rate [22]. An RCT showed that TXA was associated with reduced intraoperative bleeding but not hemoglobin change in patients with epidural, subdural, and intraparenchymal hemorrhage [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…If TXA is used as soon as possible after trauma, TXA may reduce death rate on mild to moderate TBI patients without increasing occlusive vascular event risk. In additionally, Ebrahimi et al 24) reported that TXA may reduce surgery related bleeding in patient with SDH and EDH. Mean amount of bleeding during surgery was lower in receiving TAX groups compared to the placebo groups.…”
Section: Critical Care Of Asdhmentioning
confidence: 98%
“…Two authors independently abstracted data and assessed the quality of evidence. We extracted the following information from included studies [13][14][15][16][17][18][19][20][21][22][23][24][25] : study author and years, study design, demographic data, ages and sexes of participants, details of the intervention, and risk of bias. We extracted the results of the included study as follow: mortality, severe TBI (Glasgow Coma Scale from 3 to 8), unfavorable Glasgow Outcome Scale (GOS < 4), neurosurgical intervention, mean hemorrhage volume, the number people of new bleeding, adverse events including vascular occlusive events, pulmonary embolism (PE), deep vein thrombosis (DVT), neurological complications (including stroke and seizure), gastrointestinal bleeding, myocardial infarction, infectious complications, renal failure.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…By reading the title and abstract, 547 articles were excluded, yielding 126 studies. Of these, full text was assessed, leading to the exclusion of another 113 studies, resulting in 13 studies that were included in the analysis [13][14][15][16][17][18][19][20][21][22][23][24][25] . Studies were conducted in patients undergoing TBI patients.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation